The Effectiveness of @Infotasik Instagram Content on Fulfilling Followers' Information Needs - Astri Lestari Agustin; Adrio Kusmareza Adim (PT Mattawang Mediatama Solution, 2023)
In today's society, the reliance on social media as a primary source of information has increased due to its rapid dissemination and easy accessibility anytime and anywhere. Numerous individuals, organizations, companies, governments, and academic institutions worldwide have utilized Instagram as a platform for distributing relevant and easily consumable information. Instagram facilitates the search for information about specific regions or cities, including their cuisine, traffic conditions, local government policies, tourist attractions, and societal phenomena. This research examines the effectiveness of the @infotasik Instagram account in fulfilling the information needs of its followers. The objective is to determine to what extent the content of the @infotasik account is effective in meeting the information needs of its followers. A quantitative research method was employed for this study. The population for this research comprised the followers of the @infotasik Instagram account, with a sample size of 100 individuals selected using purposive sampling technique. The research design falls under the category of descriptive quantitative research, intended to test specific hypotheses. Survey methodology was adopted, where a questionnaire link was distributed to active Instagram users who were followers of @infotasik through direct messages. The study concludes that the content of the @infotasik Instagram account is effective in fulfilling the information needs of its followers, as it provides credible and consistent dissemination of in-depth information that is accurate, comprehensive, and specific in addressing the followers' information requirements.